2020
DOI: 10.1186/s13041-020-0559-8
|View full text |Cite|
|
Sign up to set email alerts
|

Toll-like receptor 4 deficiency ameliorates β2-microglobulin induced age-related cognition decline due to neuroinflammation in mice

Abstract: Toll-like receptor 4 (TLR4) is a crucial receptor in neuroinflammation and apoptotic neuronal death, and increasing evidences indicated that β2-microglobulin (B2M) is thought to be a major contributor to age-related cognitive decline. In present study, we designed to investigate the effects of TLR4 on B2M-induced age-related cognitive decline. Wild-type (WT) C57BL/6, TLR4 knockout (TLR4-KO) mice and hippocampal neurons from the two type mice were respectively divided into two groups: (1) Veh group; (2) B2M-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 53 publications
3
22
0
Order By: Relevance
“…In the MWM detection, we found that the latency time of KO mice was significantly reduced compared with WT mice at the second navigation test day. It indicated that KO mice had stronger adaptive ability and memory ability, which was consistent with a previous study that TLR4 deficiency ameliorated cognition decline due to neuroinflammation in mice ( Zhong et al, 2020 ). Following SAH model induced on day 6, the escape latency of WT mice was longer than that of the TLR4 deficiency mice on day 7.…”
Section: Resultssupporting
confidence: 91%
“…In the MWM detection, we found that the latency time of KO mice was significantly reduced compared with WT mice at the second navigation test day. It indicated that KO mice had stronger adaptive ability and memory ability, which was consistent with a previous study that TLR4 deficiency ameliorated cognition decline due to neuroinflammation in mice ( Zhong et al, 2020 ). Following SAH model induced on day 6, the escape latency of WT mice was longer than that of the TLR4 deficiency mice on day 7.…”
Section: Resultssupporting
confidence: 91%
“…TLR4 knockout inhibits the expression of inflammatory factors IL-1 β and TNF- α and improves the survival rate after induction of intracerebral hemorrhage (ICH) compared with wild-type (WT) mice [ 108 ]. TLR4 deficiency suppresses the inflammatory factors IL-1 β and TNF- α and improves cognitive dysfunction in β 2-microglobulin- (B2M-) induced age-related cognitive decline compared with WT mice [ 109 ]. Moreover, several studies have demonstrated that SIRT1 regulates neuroinflammation via inhibition of the TLR pathway.…”
Section: Sirt1 and Neuroinflammationmentioning
confidence: 99%
“…39 TLR4 is one of the most representative TLRs and has been extensively studied. In the brain, TLR4 is involved in learning and memory, 40 aging, 41 mood, 42 and neurodegenerative diseases such as Parkinson's disease 43 and Alzheimer's disease. 23,44 MyD88 is a common linker protein for all TLRs except TLR3.…”
Section: Bodv-1 Upregulates Tlr4 Myd88 and Irf5 Expression In The Rat Hippocampusmentioning
confidence: 99%